Climate‐Based Emulator of Distant Swell Trains and Local Seas Approaching a Pacific Atoll. Issue 6 (21st June 2021) - Cagigal, Laura; Rueda, Ana; Ricondo, Alba; Pérez, Jorge; Ripoll, Nicolás; Coco, Giovanni; Méndez, Fernando J.
Abstract: Wave‐induced flooding is a major coastal hazard for the low‐lying atolls of the Pacific. These flooding events are expected to increase over time, which may cause significant coastal damage in some locations. Coastal flooding analysis (forensic or forecasted) is particularly challenging in these small islands due to the co‐occurrence of several swells and local seas propagating in a complex configuration of archipelagos. Therefore, assessing the contribution of swells and wind seas on the flooding hazards that threaten the atoll islands requires the spectral characterization of the wave climate, since integrated wave parameters do not accurately represent the wave conditions in these environments. On the other hand, the relative short records of wave conditions, represent only a small fraction of the possible range of combinations that could produce a wave‐induced flooding event. For these reasons, we propose the analysis of all the spectral energy arriving toward a study site, by isolating and parameterizing each swell train. Then, taking into account the link with large‐scale climatic patterns (i.e., El Niño Southern Oscillation), we present a new multi‐modal seas emulator capable of generating infinitely long time series of synthetic individual swell trains and seas. This new climate‐based emulator allows a better understanding of swell behavior in the Pacific, and the generation of multimodal wave conditions to populate the historical records as a key point to perform robust coastal flood risk assessments considering climate variability. Plain Language Summary: Coastal flooding events generated by waves are a key issue for low‐lying Pacific atolls. Those events are expected to increase over time due to climate change and in order to be prepared, it is important to study where those waves are generated. As those atolls are located in the middle of a large ocean, where concurrent waves approach from every direction, we need to use the wave spectrum which characterizes the distribution of energy at different directions and frequencies. We propose the analysis of Majuro, capital of the Marshall Islands, aggregating all the spectral wave energy surrounding the atoll into a "super‐point". Then, we identify the local generated waves (i.e., seas) and the individual far field generated waves (i.e., swell trains), and find its link with large scale climatic patterns (i.e., El Niño Southern Oscillation). Knowing this link, we develop a climate‐based emulator capable of generating infinitely long time series of synthetic swell trains and seas that maintain the same properties as the historical records. This new emulator allows a better understanding of swell behaviour, and the generation of multimodal wave conditions to populate the historical records in order to perform robust coastal flood risk assessments considering climate variability Key Points: A climate‐based emulator of swell trains and local seas capable to generate multimodal wave conditions is presented An algorithm to isolate and parameterize swell trains is developed and waves are linked to large‐scale climate patterns The validation of the reconstructed spectra against the hindcast confirms the capability to reproduce the historical ocean waves behavior